Exploring Fan Passions Driving Consumer Engagement: The Case of Philippine K-pop and K-drama Fans - Capistrano, Erik Paolo (Archīum Ateneo, 2024)
This research1 presents two main streams of discourse on managing an interesting cultural export product that has earned phenomenal worldwide attention: (1) The influence of fan passions on consumer engagement (CE) behaviors; and (2) the theoretical and practical value of perceiving CE as a process, analyzed within the context of the Hallyu, or Korean Wave, phenomenon, specifically for K-pop and K-drama fans. Analyzing 6,755 survey responses from Philippine fans, the multiple regression results find that fan passions are indeed favorably significant drivers of online CE behaviors of pop cultural content consumption, community formation, conversation making, and commerce behaviors. Furthermore, this research lends empirical support that pop cultural content consumption is central to this CE process. Additional bootstrapping analyses show that this process is not strictly linear, and that other phases within the process can amplify each other to produce more favorable behaviors and outcomes. This research provides quantitative empirical results supporting key areas for scholars regarding the application of theory-based CE on particular pop cultural products and consumer segments, and for organizations on how to strategize towards maximizing the benefits of good CE management involving pop cultural product consumption.2